Lansium domesticum metabolites interfere with digestive enzyme function in the rice weevil sitophilus oryzae - Yadi Oktariansyah; Ferta Liza Putri; Yuniar Harvianti; Eva Musifa (JPBIO (Jurnal Pendidikan Biologi), 2026)
Pectin methylesterase (PME) plays a key role in polysaccharide digestion in the rice weevil Sitophilus oryzae, making it a potential molecular target for pest control. This study employed structure-based in silico analysis to evaluate selected metabolites of Lansium domesticum as PME inhibitors. Representative compounds were chosen according to predicted interference mechanisms and docked into the validated catalytic site. All complexes showed structural stability, while interaction patterns revealed six inhibition modes: competitive mimicry, catalytic disruption, orientation interference, channel blocking, polymer mimicry, and interfacial modulation, whereas polyphenols and glycosides produced the strongest interference. The findings indicate that L. domesticum metabolites can disrupt digestive enzymatic processes through multiple complementary pathways, supporting their potential development as biologically derived pest management agents.